Integrasi Ekoteologi Islam dan Wakaf: Menyelaraskan Nilai-Nilai Keagamaan dengan Aksi Ekologis - Rizqi Anfanni Fahmi (Universitas Muhammadiyah Jember, 2025)
This study analyzes the application of Waqf in environmental conservation projects, focusing on its potential and challenges in supporting ecological sustainability. A Narrative Review approach was employed, examining relevant literature from the Scopus database with keywords ekoteologi, Islamic endowment, and Waqf. The results indicate that Waqf has significant potential in financing sustainable environmental projects such as forest conservation, water resource management, and urban greening. Waqf-funded projects contribute to environmental preservation and enhance social and spiritual awareness. However, challenges include management issues, unclear legal frameworks for ecological use, and limited management capacity. The study recommends institutional reforms, policy updates, and improved transparency in Waqf fund management. The findings contribute to understanding how Waqf can be an effective financing tool for environmental sustainability and strengthen the synergy between religious teachings and ecological actions.